Peningkatan Pemahaman Materi Bulutangkis Melalui Media Interaktif Google Sheet Siswa Kelas VII SMPN 1 Kota Kediri - Risqi Bustanul Arifin; Mokhamad Firdaus; Danang Kanda Riyatmojo (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to develop basic badminton skills in grade VII students at SMP Negeri 1 Kediri City by utilizing interactive learning media. The approach applied is Classroom Action Research (CAR) which is carried out in two cycles, where each cycle includes the planning, implementation, observation, and evaluation stages. Participants in this study were 32 students who faced challenges in mastering these skills. mastering basic badminton techniques, such as racket grip, footwork, service, and basic strokes. The research instruments included observation sheets, skill tests, and interest and motivation questionnaires. The study revealed significant progress in basic badminton skills, where the average score increased from 65.78 in Phase I to 72.78 in Phase II, or an increase of 10.64%. Interactive media, such as video tutorials and movement simulations, have proven effective in improving students' understanding and motivation. In conclusion, the use of digital platforms not only enriches students' abilities but also provides a more interesting and dynamic learning environment.